Pengaruh Vatiabel Pembangunan Berkelanjutan Terhadap Pertumbuhan Ekonomi Di Asia Timur Tahun 2014-2018 - Putri, Syafika Putri; Cahyono, Hendry (Independent: Journal of Economics, 2022)
The purpose of this study is to aim the effect of sustainable development variables on economic growth in the East Asia. The period used in this research is 2014-2018. This study uses a quantitative approach. The population research includes Sustainable Development considers the effects of CO2 emissions, foreign direct investment (FDI), domestic credit, international tourism arrival, agriculture, fishery, education, trade and forestry on economic growth in East Asia 2014-2018. By using purposive sampling technique. The data analysis method used is the Panel Data Regression. The findings of this research showed that there are six variables of sustainable development that show positif and significant results. Such as foreign direct investment (FDI), domestic credit, international tourism arrival, agriculture, fishery, education, trade and forestry. CO2 emissions result show negative and significant on economic growth. Keywords: Sustainable Development, Economic Growth, Panel Data Regression